PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP LOYALITASMUZAKKI PADA BAITUL MAAL HIDAYATULLAH (BMH) PERWAKILANBENGKULU - Hendri; Hendri, Hendri (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
This study aims to analyze the effect of each variable, namely the Effect ofAccountability and Transparency on Muzakki's Loyalty at Bengkulu's Baitul Maal Hidayatullah(BMH) Representative. As a nonprofit organization, the Amil Zakat Institution needs to payattention to accountability and transparency to muzakki loyalty. In this study data was collectedthrough a questionnaire distributed at the Baitul Maal Hidayatullah (BMH) BengkuluRepresentative. Respondents in this study were muzakki BMH. The number of samples whosedata was successfully processed was 84 muzakki. The sample selection method used is anonprobability method, namely convience sampling which is a sampling technique based on theease of accessing members of the population.The results of hypothesis testing indicate that there is a positive effect of transparencyon muzakki loyalty. This means that the higher the transparency of the institution, the higher themuzakki loyalty to Baitul Maal Hidayatullah (BMH) Bengkulu Representative.